Hypotension after general anaesthesia induction using remimazolam or propofol in geriatric patients undergoing sevoflurane anaesthesia with remifentanil: a single-centre, double-blind, randomised controlled trial - Takaki, Ryuki; Yokose, Masashi; Mihara, Takahiro; Saigusa, Yusuke; Tanaka, Hiroyuki; Yamamoto, Natsuhiro; Masui, Kenichi; Goto, Takahisa (British journal of anaesthesia : BJA, 2024)
The occurrence of hypotension after induction of general anaesthesia is common in geriatric patients, and should be prevented to minimise perioperative complications. Compared with propofol, remimazolam potentially has a lower incidence of hypotension. This study aimed to compare the incidence of hypotension after general anaesthesia induction with remimazolam or propofol in geriatric patients. This single-centre, double-blind, randomised trial enrolled 90 patients aged ≥80 yr who received general anaesthesia for scheduled surgery. Patients were randomised to receive remimazolam (12 mg kg−1 h−1) or propofol (0.025 mg kg−1 s−1) for anaesthesia induction, with remifentanil and sevoflurane. The presence or absence of hypertension on the ward served as the stratification factor. The incidence of hypotension after the induction of general anaesthesia, defined as a noninvasive mean arterial pressure of <65 mm Hg measured every minute from initiation of drug administration to 3 min after tracheal intubation, was the primary outcome. Subgroup analysis was performed for the primary outcome using preoperative ward hypertension, clinical frailty scale, Charlson Comorbidity Index, and age. Three subjects were excluded before drug administration, and 87 subjects were included in the analysis. The incidence of hypotension was 72.1% (31/43) and 72.7% (32/44) with remimazolam or propofol, respectively. No statistically significant differences (adjusted odds ratio, 0.96; 95% confidence interval, 0.37–2.46; P=0.93) were observed between groups. Subgroup analysis revealed no significant differences between groups. Compared with propofol, remimazolam did not reduce the incidence of hypotension after general anaesthesia induction in patients aged ≥80 yr. UMIN000042587.